Pengaruh bahan bonding self-etch terhadap kekuatan perlekatan antara pasak glass fiber dengan resin komposit - Astrid Yudhit; Rusfian Dayuni Ariski S (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Nowadays, glass fiber post and composite resin cores have been used in endodontic treatment for esthetics achievement. The success of this treatment was affected by some factors such as bond strength between post and cores. The aim of this study is to investigate the effect of self etch bonding agent that use as adhesive materials between glass fiber post and resin composite by its bond strength. Totally twenty samples is used in this study, and divided in two groups (n=10 for each group), bonding group agents and without bonding agent group (control). The tensile-shear bond strength tested with Universal Testing Machine. Then, the bond strength values were analyzed statistically with t-test (p≤ 0,05). The result shows that bonds strength values in bonding agent groups were higher than without bonding agent groups. But, there is no significantly different between groups. In conclusion, bonding agent did not have effect on tensile-shear bond strength between glass fiber post and resin composite.